Facade conservation of Kuala Lumpur shop houses in relation with new development / Norlin Ibrahim - Ibrahim, Norlin (Universiti Teknologi MARA, Shah Alam, 2001)
The importance of conservation and preservation act toward the historical buildings has already been recognised in our country during the last decade. The term is popular only among the professional whom involves in building construction (i.e.: architects and designers), archaeologist and other individual conservationist. However, the acceptance among the community or lay-man arestill doubtful. The preservation of the historic buildings are important because it gave the city its character, continuity and pride. The conservation act did not intend to stop the process of development, so new development should see the restriction as a challenge to creativity, and not otherwise. The restriction also does not mean to duplicate the style of old buildings but should find appropriate and harmonious relationships to control volume, scale, colour, material and textures. The regulation becomes crucial especially when the new development took place in the urban area. The new design should be related to the existing architecture to avoid chaotic visual quality. If we took a city as one big painting then we could understand the importance of this relationship between old and new. The city potrey the nation pride and identity, it is more than just an assets,it is 'US'.